1985
DOI: 10.1095/biolreprod32.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies on the Localization of Cellular Retinol-Binding Protein in Rat Testis and Epididymis

Abstract: The immunohistochemical localization of cellular retinol-binding protein (CRBP) was studied in rat testis and epididymis. Parallel studies were also carried out on the localization of plasma retinol-binding protein (RBP) and transthyretin (TTR) in testis. The studies employed antibodies purified by immunosorbent affinity chromatography, permitting the specific staining and localization of each antigen by the unlabeled peroxidase-antiperoxidase method. For RBP and TTR, specific immune staining was found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
6

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 47 publications
3
36
0
6
Order By: Relevance
“…Previously, rat ALDH1A1 has been shown to recognize holo-CRBP1 as a substrate ( 9 ), but the effect of CRBP1 on at RA formation by human ALDH1A enzymes has never been reported. Similarly CBRP1 expression in the Sertoli cells of rats ( 42 ) has been shown suggesting that CRBPs play an important role in modulating intratesticular RA metabolism. While ALDH1A1 was predicted to be the major contributor to at RA formation in the absence of CRBPs, when the inhibition of ALDH1A1 and activation of ALDH1A2 by CRBP1 was accounted for, ALDH1A2 was predicted to be the predominant enzyme forming at RA in the testis.…”
Section: Correlation Of Intratesticular Ra Concentrations With Aldh1amentioning
confidence: 80%
“…Previously, rat ALDH1A1 has been shown to recognize holo-CRBP1 as a substrate ( 9 ), but the effect of CRBP1 on at RA formation by human ALDH1A enzymes has never been reported. Similarly CBRP1 expression in the Sertoli cells of rats ( 42 ) has been shown suggesting that CRBPs play an important role in modulating intratesticular RA metabolism. While ALDH1A1 was predicted to be the major contributor to at RA formation in the absence of CRBPs, when the inhibition of ALDH1A1 and activation of ALDH1A2 by CRBP1 was accounted for, ALDH1A2 was predicted to be the predominant enzyme forming at RA in the testis.…”
Section: Correlation Of Intratesticular Ra Concentrations With Aldh1amentioning
confidence: 80%
“…Each' of these proteins was found to be localized in specific cells within each organ. Highly specific localization of CRBP has also been observed in the testis and epididymis (8,9). These studies provide information concerning the specific cells and anatomic loci, within different organs, where retinol and/or its binding proteins may be playing important biological roles.…”
mentioning
confidence: 74%
“…*The islet values given in this column are considered less accurate than the values given in units of ug/mg of protein, because of the lower accuracy inherent in the estimate of the wet weight of the islets studied. These values are, however, useful for comparison with values available for other tissues in these units (9,10,20,31).…”
Section: Discussionmentioning
confidence: 99%
“…The Sertoli cells of the testes and the retinal pigment epithelium (RPE) of the eye contain tight junctions between adjacent cells, forming the blood-testes and part of the blood-retina barriers, respectively. Sertoli cells and RPE cells contain high levels of CRBP (3)(4)(5). The presence of CRBP within four different cell types comprising separate blood-organ barriers strongly suggests a common functional link for CRBP in these cells.…”
Section: Cellular Localization Of Crbp By Immunohistochemicalmentioning
confidence: 99%
“…A cytoplasmic protein termed cellular retinol-binding protein (CRBP) may then transport the internalized retinol through the aqueous milieu of the cytoplasm to intracellular sites of action or metabolism (2). Studies of the retina (3) and testes (4,5) have demonstrated high levels of CRBP in some of the cells that form the blood-retina and blood-testis barriers, suggesting a role for CRBP in the transcellular movement of retinol across these blood-organ barriers. CRBP is present in human (6) and rat (7,8) brain and further fixed for 1 hr in cacodylate-buffered 1% osmium tetroxide, dehydrated, and embedded in Araldite 502 (CIBA Pharmaceutical).…”
mentioning
confidence: 99%